What is reformed theology? Understanding the basics - Sproul, R. C. (Robert Charles) (Grand Rapids Baker Books, 2005)
Founder of Ligonier Ministries and author of more than ninety books introduces readers to the distinctives of Reformed theology in this timeless and valuable resource.
Keywords: Theology, Doctrinal -- Popular works. Reformed Church -- Doctrines. Theology, Doctrinal